Public Relations Strategy in Improving the Image of East Java Bappeda: A Review of Its Digitalization Strategy - Alvinda Rizka Awalin; Salsabila Wanda Putri Damayanti; Hanifah Mufidatul Ilmi; Ruri Nurul Aeni Wulandari; Durinta Puspasari (Universitas Negeri Surabaya, 2024)
This research aims to analyze the strategies used in digitalization to improve the image of East Java Bappeda. This research uses qualitative methods with data collection techniques using interviews and observation. The informants in this research were employees of the multimedia division who also have public relations roles and already have experience in this field. The indicators used in this research are fact-finding, planning, action and communication, and evaluation. The research results show that public relations at East Java Bappeda is more active in utilizing digital media, such as Instagram and websites, to improve the agency's image. The strategies implemented by prioritizing aspects of information disclosure according to facts packaged using post designs that are attractive, contemporary and have philosophical value are actually quite effective. However, in terms of engagement statistics, Instagram is considered to be less effective in attracting people's activity, and the same goes for the website. Nevertheless, a comprehensive evaluation can help the Public Relations of East Java Bappeda to improve, reorganize, and innovate in creating more optimal strategies in an effort to maintain a positive reputation, improve the image, and strengthen public trust in East Java Bappeda.